Melt Viscoelastic Assessment of Poly(Lactic Acid) Composting: Influence of UV Ageing - Verney, Vincent; Ramoné, Audrey; Delor-Jestin, Florence; Commereuc, Sophie; Koutny, Marek; Perchet, Geoffrey; Troquet, Julien (Molecules (Basel, Switzerland), 2018)
This study is devoted to the degradation pathway (bio, photo degradation and photo/bio) of Poly(Lactic acid) PLA polymers by means of melt viscoelasticity. A comparison was made between three PLA polymers with different microstructures (L, D stereoisomers). Biodegradability was determined during composting by burying the polymer films in compost at 58 °C. Melt viscoelasticity was used to assess the molecular evolution of the materials during the composting process. Viscoelastic data were plotted in the complex plane. We used this methodology to check the kinetics of the molecular weight decrease during the initial stages of the degradation, through the evolution of Newtonian viscosity. After a few days in compost, the Newtonian viscosity decreased sharply, meaning that macromolecular chain scissions began at the beginning of the experiments. However, a double molar mass distribution was also observed on Cole⁻Cole plots, indicating that there is also a chain recombination mechanism competing with the chain scission mechanism. PLA hydrolysis was observed by infra-red spectroscopy, where acid characteristic peaks appeared and became more intense during experiments, confirming hydrolytic activity during the first step of biodegradation. During UV ageing, polymer materials undergo a deep molecular evolution. After photo-degradation, lower viscosities were measured during biodegradation, but no significant differences in composting were found.
Keywords: Polymers; biodegradation; rheology; molekulová hmotnost; Molecular Weight; PLA; photo-degradation; Polyesters; kinetika; Biodegradation, Environmental; Viscosity; polymery; Kinetics; Viscoelastic Substances; viskozita; biodegradace; viskoelastické látky; polyestery